Awareness of over the counter antibiotics to combat antimicrobial resistance - Patil, Sunita Sunil; Agarwal, Saket (International Journal of Basic & Clinical Pharmacology, 2019)
Background: In India there is wide use of over the counter (OTC) antibiotics and unawareness of its harmful effects. In India dispensing antibiotics without prescription is a major contribution factor in development of antimicrobial resistance (AMR). The objectives of the present study were to evaluate awareness and proper use of OTC antibiotics in the community. Methods: Responses to a questionnaire covering various aspects on awareness and usage of OTC antibiotics were obtained from 100 families and 100 pharmacy shops in the community by second year MBBS students after permission from institutional ethical committee. The study period was from January 2019 to June 2019. Results: Among 100 responders 78% used OTC antibiotics for frequently reported illness like common cold (58%), body- ache (19%), fever (13%) and cough (10%). Most common reason for using OTC antibiotic is to avoid high consultation fees (64%).76% pharmacy dispense antibiotics without prescription. 60% pharmacy unaware of increase chance of developing resistance due to OTC antibiotics. 80% pharmacy maintain register book and were aware of laws and regulations of OTC prescription but still 70% dispense drugs due to fear of losing sales and profit. 50% pharmacy said they encourage patients to consult the physician and get the prescription. Most common antibiotic sold without prescription is amoxicillin (51%) and azithromycin (38%). Conclusions: We have identified unawareness among people about use and harmful effects of using OTC antibiotics. Also pharmacies are not following rules and regulations for OTC drugs. So our aim is to increase public knowledge of proper use and harmful effects of OTC antibiotics and help our global program to reduce AMR.